Diet scores and cardio-metabolic risk factors among Guatemalan young adults - Gregory, Cria O. (2008)
We assessed the association of four diet quality scores with multiple cardio-metabolic outcomes among Guatemalan young adults experiencing the nutrition transition. We obtained cross-sectional dietary, demographic, anthropometric and cardio-metabolic risk factor data from 1220 Guatemalan adults (mean age 32·7 (SD 5·8) years) in 2002–4, and computed a Recommended Food Score (RFS), Not Recommended Food Score (NRFS), Food Variety Score (FVS) and the Dietary Quality Index-International (DQI-I). All four scores were correlated with energy intake (r 0·23–0·49; all P<0·01), but had varying associations with socio-demographic characteristics, lifestyle factors and nutrient intakes. None of the scores was inversely associated with the metabolic syndrome or its components; rather some were positively associated with risk factors. Among both men and women the DQI-I was positively associated with BMI (kg/m(2); β = 0·10, 95 % CI 0·003, 0·21 (men); β = 0·07, 95 % CI 0·01, 0·14 (women)) and waist circumference (cm; β = 0·02, 95 % CI 0·01, 0·03 (men); β = 0·02, 95 % CI = 0·01, 0·02 (women)). Among men, the RFS was positively associated with TAG (mg/l; β = 0·11, 95 % CI 0·02, 0·21) and glucose (mg/l; β = 0·13: 95 % CI 0·03, 0·22). We conclude that indices of diet quality are not consistently associated with chronic disease risk factor prevalence in this population of Guatemalan young adults.